2016
DOI: 10.1016/j.jval.2016.08.533
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Economic Impact Due to Productivity Losses of Diabetes and Major Depressive Disorder in Singapore: Human Capital Versus Friction cost Approaches

Abstract: The calculation approach (HC vs FC) can have a substantial impact on the estimates. Incorporation of productivity losses into decision-making for healthcare interventions would need to carefully consider which approach is most appropriate for Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The HC approach assumes that lost productive time is not compensated for by other workers or by work outside normal hours, which may not fully reflect reality. While there is no definitive agreement among health economists as to the most appropriate approach to take when estimating productivity losses, it has been demonstrated that alternative approaches, including the friction cost (FC) approach, may lead to lower estimates of productivity losses than the HC approach . However, the FC methodology cannot be used to estimate productivity losses due to presenteeism and given that presenteeism had a larger impact on productivity losses than absenteeism in the present study, we feel that the HC approach was appropriate for this analysis.…”
Section: Discussionmentioning
confidence: 80%
“…The HC approach assumes that lost productive time is not compensated for by other workers or by work outside normal hours, which may not fully reflect reality. While there is no definitive agreement among health economists as to the most appropriate approach to take when estimating productivity losses, it has been demonstrated that alternative approaches, including the friction cost (FC) approach, may lead to lower estimates of productivity losses than the HC approach . However, the FC methodology cannot be used to estimate productivity losses due to presenteeism and given that presenteeism had a larger impact on productivity losses than absenteeism in the present study, we feel that the HC approach was appropriate for this analysis.…”
Section: Discussionmentioning
confidence: 80%
“…The burden of chronic non-communicable diseases, especially diabetes, is an issue of increasing concern to governments. Many studies have researched the impact of diabetes on productivity losses at the global level [10] and country level [11][12][13][14][15][16][17][18][19]. Given the significant productivity losses due to diabetes in other countries, there are surprisingly few studies about diabetes productivity losses in China.…”
Section: Introductionmentioning
confidence: 99%
“…(US$1) million in Norway [19]. In Singapore, the productivity losses due to diabetes was US$139.3 million, made up of US$27.1 million for absenteeism and presenteeism, and US$112.2 million for premature mortality death in 2016 [20].…”
Section: Introductionmentioning
confidence: 99%